2018
DOI: 10.1007/s11655-018-2560-y
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Application of Complementary and Alternative Medicine in Chinese Patients with Parkinson’s Disease: A Pilot Study

Abstract: CAMs, especially Chinese materia medica, rehabilitation exercise, and acupuncture, are widely used for PD patients in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…According to the results of the present study, among the participants who were willing to accept TCM, 70.51% preferred Chinese herbal medicine, 62.79% chose Chinese patent medicine, and 34.96% favored massage treatment. A survey on patients with Parkinson disease in China illustrated that herbal medicine, rehabilitation exercise, and acupuncture were the most commonly used TCM therapies [ 38 ]. Compared to other TCM therapies, Chinese herbal medicine is the most popular treatment in China.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the present study, among the participants who were willing to accept TCM, 70.51% preferred Chinese herbal medicine, 62.79% chose Chinese patent medicine, and 34.96% favored massage treatment. A survey on patients with Parkinson disease in China illustrated that herbal medicine, rehabilitation exercise, and acupuncture were the most commonly used TCM therapies [ 38 ]. Compared to other TCM therapies, Chinese herbal medicine is the most popular treatment in China.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that acupuncture is widely used for Chinese patients with PD ( 7 ). Additionally, our previous clinical observation indicates that QHN therapy may have sustained effects, which may be superior to other acupuncture approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has existed for over 4,000 years as one of the main treatments of traditional Chinese medicine. As an adjuvant therapy, acupuncture is widely used in the treatment of PD, particularly in East Asia ( 7 ). Numerous clinical trials have shown that acupuncture could improve motor symptoms and the quality of sleep, reduce the dose and frequency of anti-PD drugs, and alleviate their side effects ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, 48.6% of patients underwent CAM treatment and herbal medication, primarily rehabilitation exercise and acupuncture. These treatments were effective in half of the patients who received them, while they produced negative results in 11% of the patients (Pan et al, 2018). Additionally, the incidence and prevalence of PD in Asian countries, including South Korea, have been shown to be lower than in Europe and America (Pringsheim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%